Variability of adenoidectomy/tonsillectomy rates among children of the Veneto Region, Italy - Andretta Marilisa; Zambon Francesco; Avossa Francesco; Marchesan Maria; Fedeli Ugo; Baussano Iacopo; Spolaore Paolo (BMC Health Services Research, 2009)
Abstract Background Despite national guidelines in 2003 aimed at limiting the recourse to tonsillectomy and/or adenoidectomy (A/T), the latter are among the most frequent pediatric surgeries performed in Italy. Aim of the study is to investigate variability of A/T rates among children of the Veneto Region, Italy. Methods All discharges of Veneto residents with Diagnosis-Related Groups 57–60 and ICD9-CM intervention codes 28.2 (tonsillectomy), 28.3 (adenotonsillectomy), 28.6 (adenoidectomy) were selected in the period 2000–2006 for a descriptive analysis. A multilevel Poisson regression model was applied to estimate Incidence Rate Ratios (IRR) with 95% Confidence Intervals (CI) for A/T surgery among children aged 2–9 years in 2004–2006, while taking into account clustering of interventions within the 21 Local Health Units. Results Through 2000–2006, the overall number of A/T surgeries decreased (-8%); there was a decline of adenoidectomies (-20%) and tonsillectomies (-8%), whereas adenotonsillectomies raised (+18%). Analyses on children aged 2–9 resulted in an overall rate of 14.4 surgeries per 1000 person-years (16.1 among males and 12.5 among females), with a wide heterogeneity across Local Health Units (range 8.1–27.6). At random intercept Poisson regression, while adjusting for sex and age, intervention rates were markedly lower among foreign than among Italian children (IRR = 0.57, CI 0.53–0.61). A/T rates in the 10–40 age group (mainly tonsillectomies) computed for each Local Health Unit and introduced in the regression model accounted for 40% of the variance at Local Health Unit level of pediatric rates (mainly adenoidectomies and adenotonsillectomies). Conclusion A/T rates in the Veneto Region, especially adenoidectomies among children aged 2–9 years, remain high notwithstanding a decrease through 2000–2006. A wide heterogeneity according to nationality and Local Health Units is evident. The propensity to A/T surgery of each Local Health Unit is similar in different age groups and for different surgical indications.